Pengaruh Model Deteksi Dini Kartu Kendali Stroke terhadap Kemampuan Klien dalam Pengendalian Faktor Resiko Stroke - Tarwoto Tarwoto (Syntax Corporation Indonesia, 2021)
Stroke is a degenerative disease that currently occurs as much as it occurs. This is due to changes in people's unhealthy lifestyles, such as reduced activity, unhealthy diet, lack of rest, and many other factors. The general purpose of this study is to identify the influence of stroke control card education on the client's ability to control stroke risk factors. In this study using Quasi-Experimental with Pretest-Posttest with Control Group Desaign approach. In this design, researchers conducted an assessment on the control group and intervention group before stroke control card (KKS) education. The intervention group was treated with KKS education, then measured (post test) the level of knowledge ability and attitude to control stroke risk factors while the control group was not treated but measured. This study is titled the influence of early detection models through stroke control card education on the client's ability to control stroke risk factors. The study sampled 80 people for the control group and 80 people in the intervention group with the criteria of the sample of patients with stroke risk factors. Research site in South Jakarta with a research duration of 4 months.